Advancements and outcomes of robotic-assisted surgery in pediatric patients: a multicenter analysis - Mattioli, Girolamo; Rotondi, Giulia; Avanzini, Stefano; Torre, Michele; Brenco, Gaia; Romeo, Carmelo; Molinaro, Francesco; Prestipino, Marco; Cheli, Maurizio; Lacanna, Francesco; Paoli, Gabriella; Cincotti, Silvano; et al. (Frontiers in Pediatrics, 2025)
BackgroundRobotic surgery (RS) has gained widespread adoption in adult surgical specialties but faces unique challenges in pediatric applications due to anatomical, technical, and economic factors. This multicenter study evaluates the feasibility, clinical outcomes, and organizational implications of implementing robotic-assisted surgery in pediatric patients across various surgical disciplines.MethodsData were retrospectively collected from 569 pediatric patients undergoing RS between 2015 and 2016 and 2020–2025 at five Italian pediatric surgery centers. Procedures included urological, gastrointestinal, oncological, and thoracic surgeries. Patient demographics, operative details, complications, and conversion rates were analyzed. Standardized operating room setups and trocar placements were developed to optimize surgical ergonomics.ResultsThe median patient age was 73.8 months (range 4–575.3 months), with 9.3% weighing less than 10 kg. Urological procedures comprised 47.2% of cases, with a 0.7% conversion rate to open surgery. Gastrointestinal, oncological, and thoracic procedures had conversion rates of 3.9%, 27.2%, and 13.5%, respectively. Postoperative major complications occurred in 7% of cases. The study confirmed the safety and feasibility of RS even in patients with significant clinical complexity (20.5% ASA ≥3). Robotic technology provided enhanced precision, dexterity, and visualization, enabling complex reconstructions in confined anatomical spaces. Centralized care in dedicated pediatric centers was critical for successful implementation.ConclusionsRobotic surgery represents a significant advancement in pediatric minimally invasive surgery, offering clinical benefits across multiple specialties. Despite economic and logistical challenges, centralization and dedicated multidisciplinary teams are essential to optimize outcomes and ensure safe, sustainable adoption of robotic techniques in pediatric surgery.